A glimpse into the asog experience a historical study on the homosexual experience in the Philippines - Quintos, Jay Jomar F. (Plaridel, 2012)
In contemporary Philippine society, homosexuals are discriminated against and viewed as a comedic symbols. This is in contrast to the accounts of Philippine history which feature a wealth of tales and lore that depict homosexuals as an accepted part of the society. This paper introduces an anthropological and cultural study on the history of homosexuals from the precolonial to contemporary Philippines. It analyzes the influence of colonizers in the modern perception of homosexuals in the media today. The paper traces the early experiences and portrayals of homosexuals in the confesionarios, diccionarios, guidelines, and manuals of Spanish missionaries. These experiences and portrayals are compared to the contemporary guidelines set forth by the Movie and Television Classification and Review Board (MTRCB). In the end, this paper aims to eradicate the misconception about the modern bakla and present more of their richer traditions as asog, bayoguin, and binabayi.